The impact of having a choir in the community - Sithela, Abonga Will (College of Music, 2021)
Choir singing is something that is enjoyed by many people around the communities, some are singing in church choirs, some are singing in school choirs and some are singing in community choirs. To sustain a church choir and a school choir is relatively possible because there is some sort of support coming from these institutions as the choir serves as the secondary purpose for both these institutions. People go to church to worship the Lord and decide to join the choir, so is going to school, the learners attend school to acquire knowledge and as an extra mural activity they join the school. For the community choir, the main purpose to join a community choir is to sing for the love of music and because they are not under any institution, community choirs face many challenges that include but not limited to, the money. Amongst those challenges is the lack of knowledge about the important reason why the choirs exist, which is to build unity amongst the communities and to teach individuals the soft skills that are needed to build one's career. This study will look at contributing towards civil societies in South Africa mostly in the townships where the main focus will be developing the communities through music activities such as working with choirs from the professional point of view. Turino (2008) states that in societies around the world, music creates and expresses the emotional inner life and it also can be an avenue of money and fame. I agree with Turino, as I am also a person looking to earn my living through music. Akuno (2008) mentions that in African societies, there is music for every activity, and it does not come as a surprise that there are a lot of community choirs. In addition, music as a work of art serves physical and emotional needs while cementing psycho-social and spiritual relationships (Akuno 2008) something that is forgotten and as a result choirs face difficulty and that leads to the dissolvement of the choirs.